Association of psychological symptoms with job burnout and occupational stress among coal miners in Xinjiang, China: A cross-sectional study - Fu, Ailing; Zhao, Ting; Gao, Xiaoyan; Li, Xinze; Liu, Xin; Liu, Jiwen (Frontiers in Public Health, 2022)
Objective: The study aimed to investigate the influencing factors of psychological symptoms in relation to job burnout and occupational stress among coal miners in Xinjiang, so as to provide data support for enterprises in an effort to help them identify internal psychological risk factors and improve the mental health of coal miners. Methods: A cross-sectional study was carried out. A total of 12 coal mines were selected using the stratified cluster random sampling method and 4109 coal miners were investigated by means of online electronic questionnaires. The Symptoms Check List-90 (SCL-90), Chinese Maslach Burnout Inventory (CMBI), and Job Demand-Control (JDC) model were respectively used to measure the status of psychological symptoms, job burnout, and occupational stress among coal miners. The mediation analysis was performed through structural equation modeling (SEM) by using Analysis of Moment Structure (AMOS). Results: The prevalence of psychological symptoms was higher in the occupational stress group than in the non-occupational stress group, and increased with job burnout (P < 0.05). The multivariate logistic regression analysis results showed that mild (OR = 1.401, 95% CL: 1.165, 1.685), moderate (OR = 2.190, 95% CL:1.795, 2.672), or severe levels of burnout (OR = 6.102, 95% CL: 3.481, 10.694) and occupational stress (OR = 1.462, 95% CL: 1.272, 1.679) were risk factors for psychological symptoms in coal miners. The results of structural equation modeling indicated that occupational stress (β= 0.11, P = 0.002) and job burnout (β= 0.46, P = 0.002) had significant positive direct effects on psychological symptoms, and job burnout was an intermediate variable between occupational stress and psychological symptoms. Conclusion: High levels of job burnout and occupational stress were risk factors for psychological symptoms. Both occupational stress and job burnout had direct effects on psychological symptoms, and occupational stress could also have an indirect effect on coal miners’ psychological symptoms through the intermediate variable of job burnout.